2012
DOI: 10.1186/1476-0711-11-6
|View full text |Cite
|
Sign up to set email alerts
|

Successful salvage therapy with Daptomycin for osteomyelitis caused by methicillin-resistant Staphylococcus aureus in a renal transplant recipient with Fabry-Anderson disease

Abstract: Daptomycin is licensed in adults for the management of Staphylococcus aureus methicillin-resistant infections, including bone and skin complicated infections. We describe for the first time its use in a renal transplant recipient for Fabry-Anderson Disease with right heel osteomyelitis. The patient was unresponsive to first-line Teicoplanin and second-line Tigecycline, whereas he was successfully treated with third-line Daptomycin monotherapy at 4 mg/Kg/qd for 4 weeks. Local debridement was performed in advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
1
10
1
Order By: Relevance
“…Similar to our findings, low rates of discontinuation due to adverse effects were documented after treatment for ≥6 weeks, although dosing regimens were not elucidated in this series as in our investigation. In contrast to the current study and these previous reports, another report has documented failure of tigecycline in the acute treatment of MRSA calcaneal osteomyelitis (Polilli et al, 2012); however, this patient had also failed a previous regimen and was plagued by multiple comorbidities, making it difficult to generalize the findings. The preponderance of gastrointestinal side effects noted in our analysis is similar to that seen in prior literature (Passarell et al, 2009;Tasina et al, 2011), although we did not find a dose-response relationship.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Similar to our findings, low rates of discontinuation due to adverse effects were documented after treatment for ≥6 weeks, although dosing regimens were not elucidated in this series as in our investigation. In contrast to the current study and these previous reports, another report has documented failure of tigecycline in the acute treatment of MRSA calcaneal osteomyelitis (Polilli et al, 2012); however, this patient had also failed a previous regimen and was plagued by multiple comorbidities, making it difficult to generalize the findings. The preponderance of gastrointestinal side effects noted in our analysis is similar to that seen in prior literature (Passarell et al, 2009;Tasina et al, 2011), although we did not find a dose-response relationship.…”
Section: Discussioncontrasting
confidence: 58%
“…Finally, a case series of six patients has elucidated favorable outcomes in S. epidermidis osteomyelitis (Asseray et al, 2012). In contrast, one report has noted failure of tigecycline in an MRSA bone infection (Polilli et al, 2012). However, to our knowledge, this antibiotic has not undergone additional scrutiny in the literature regarding osteomyelitis.…”
Section: Introductionmentioning
confidence: 94%
“…In SOT patients, the most frequent bacterial targets for the use of daptomycin are S. aureus and VRE. The information available regarding the safety and efficacy of daptomycin in SOT patients is limited to case reports . In the major clinical trials with daptomycin, the drug was well tolerated and its profile of adverse effects was similar to that of the comparator drugs .…”
Section: Antimicrobial Spectrum Interactions and Adverse Effects Of mentioning
confidence: 99%
“…The published information on daptomycin administration in solid organ transplantation is limited to case studies (15,16) or retrospective cohorts in which a portion of evaluated patients were SOT recipients (17). In these studies, the drug was found to be safe and well tolerated for an extended duration of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Six patients (13.9%) ended treatment on an outpatient regimen. Treatment was administered for a median duration of 12 days (IQR [8][9][10][11][12][13][14][15][16][17][18][19][20]. Co-infection with gram-negative rods was diagnosed in 15 (34.9%) patients, mainly corresponding to Pseudomonas aeruginosa (6 patients), and Escherichia coli, Klebsiella pneumoniae, and Enterobacter cloacae, with 2 patients each.…”
Section: Treatment Featuresmentioning
confidence: 99%